Enforcement and Corporate Governance - Berglöf, Erik; Claessens, Stijn (World Bank, Washington, D.C., 2013)
Enforcement more than regulations, laws-on-the-books, or voluntary codes is key to effective corporate governance, at least in transition and developing countries. Corporate governance and enforcement mechanisms are intimately linked as they affect firms' ability to commit to their stakeholders, in particular to external investors. The authors provide a framework for understanding these links and how they are shaped by countries' institutional contexts. When the general enforcement environment is weak and specific enforcement mechanisms function poorly, as in many developing and transition countries, few of the traditional corporate governance mechanisms are effective. The principal consequence in these countries is a large block-holder, but there are important potential costs to this mechanism. A range of private and public enforcement "tools" can help reduce these costs and reinforce other supplementary corporate governance mechanisms. The limited empirical evidence suggests that private tools are more effective than public forms of enforcement in the typical environment of most developing and transition countries. However, public enforcement is necessary regardless, and private enforcement mechanisms often require public laws to function. Furthermore, in some countries at least, bottom-up, private-led tools preceded and even shaped public laws. Political economy constraints resulting from the intermingling of business and politics, however, often prevent improvements in the general enforcement environment, and adoption and implementation of public laws in these countries.